2015
DOI: 10.1517/14712598.2015.1068755
|View full text |Cite
|
Sign up to set email alerts
|

Bone and cartilage regeneration with the use of umbilical cord mesenchymal stem cells

Abstract: MSCs from umbilical cords have to be more extensively studied and the mechanisms underlying their differentiation have to be clarified. To date, they seem to be an attractive alternative to BM-MSCs. However, further research with suitable scaffolds and growth factors as well as with novel scaffold fabrication and culture technology should be conducted before they are introduced to clinical practice and replace BM-MSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 75 publications
0
33
0
3
Order By: Relevance
“…MSCs isolated from various sources have been investigated for their osteogenic potential. MSCs derived from fetal tissues, such as umbilical cord matrix, amniotic fluid, and umbilical cord blood (UCB) have emerged as an attractive alternative to adult MSCs, because of their higher proliferation potential, lack of donor site morbidity, and the possibility of their off-the-shelf use for the production of personalized autologous bone grafts [3,4]. …”
Section: Introductionmentioning
confidence: 99%
“…MSCs isolated from various sources have been investigated for their osteogenic potential. MSCs derived from fetal tissues, such as umbilical cord matrix, amniotic fluid, and umbilical cord blood (UCB) have emerged as an attractive alternative to adult MSCs, because of their higher proliferation potential, lack of donor site morbidity, and the possibility of their off-the-shelf use for the production of personalized autologous bone grafts [3,4]. …”
Section: Introductionmentioning
confidence: 99%
“…Besides adult BM‐MSCs, neonatal cord blood USSCs and CB‐MSCs are attractive cell sources for bone‐regenerative approaches in vivo (Handschel et al , ; Klontzas et al , ; Langenbach et al , ). Like the ‘gold standard’ BM‐MSCs, neonatal cord blood‐derived USSCs and CB‐MSCs can be differentiated in vitro into the chondrogenic and osteogenic lineages, while showing a more immature osteogenic signature in comparison to adult BM‐MSCs (Bosch et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…9 Therefore, it is believed that hUCMSCs own the characteristics of both seed cells and cytokines in the process of fabrication of tissue-engineered bone, which will be a promising choice to enhance the bioactivity of tissue-engineered bone graft. 10 Numerous researches have also shown that hUCMSCs have superior osteogenic properties attached to the scaffolds and are suitable seed cells for bone tissue engineering. 11 Given that some studies hold the osteogenic ability of hUCMSCs is weaker than that of hBMSCs, it is worthy to improve the osteogenesis ability of hUCMSCs.…”
Section: Introductionmentioning
confidence: 99%